"It's something I've committed to longer term": The impact of an immersion program for physicians on adoption of genomic medicine. Issue 3 (March 2021) - Martyn, Melissa; McClaren, Belinda; Janinski, Monika; Lynch, Elly; Cunningham, Fiona; Gaff, Clara
Highlights: Immersion appeared a successful strategy for genomic education and implementation. Physicians reported practice changes as a consequence of experiential learning. Diffusion occurred, with participants reporting peers seeking advice informally. Genomic information was actively disseminated via peer networks. Speciality physicians report becoming an expert resource for genetic professionals. Abstract: Objective: To foster implementation of genomic testing in medical care by providing a cadre of physicians with 'hands on' experience in genomics, positioning them as opinion leaders in their medical speciality. This paper presents qualitative evaluation of immediate outcomes, in particular its impact on peer interactions. Methods: Program design and delivery was informed by implementation science, behavior change and experiential learning theories. Inductive content analysis of transcribed audio-recordings from semi-structured post-project interviews with all participants (n = 12) was conducted. Results: Participants reported the immersion experience improved their genomic capability, established them as credible genomic experts within their speciality and altered their practice in genomic medicine. Participants reported strengthening and widening of peer-to-peer and interdisciplinary communication, with both passive diffusion and active dissemination of information to peers. Some also became a resource for genetic professionals. Conclusions: Genomic immersion participants described elements which support sustained integration of an innovation, including immediate changes (e.g. use of genomic tests) and wider impacts (e.g. professional networks). Practice implications: This study supports a role for immersion as a successful strategy for enhancing engagement of non-geneticist physicians in genomics. Additional study is needed to understand how immersion experiences change the delivery of genomic services at the provider, practice and health system level.